2021
DOI: 10.1136/jitc-2021-003001
|View full text |Cite
|
Sign up to set email alerts
|

Indication-specific tumor evolution and its impact on neoantigen targeting and biomarkers for individualized cancer immunotherapies

Abstract: BackgroundIndividualized neoantigen-specific immunotherapy (iNeST) requires robustly expressed clonal neoantigens for efficacy, but tumor mutational heterogeneity, loss of neoantigen expression, and variable tissue sampling present challenges. It is assumed that clonal neoantigens are preferred targets for immunotherapy, but the distributions of clonal neoantigens are not well characterized across cancer types.MethodsWe combined multiregion sequencing (MR-seq) analysis of five untreated, synchronously sampled … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…We observed 1% complete response (CR), 29% partial response (PR), 48% stable disease (SD), and 22% progressive disease (PD) at 54 weeks per RECIST v1.1 (Figure 3B-D) [24]. These outcomes were consistent with pooled results from 4 anti-PD-1 monotherapy arms in trials of previously untreated late-stage NSCLC [19][20][21][22].…”
Section: Neoantigen Burden Correlates With Ici Responsesupporting
confidence: 84%
See 2 more Smart Citations
“…We observed 1% complete response (CR), 29% partial response (PR), 48% stable disease (SD), and 22% progressive disease (PD) at 54 weeks per RECIST v1.1 (Figure 3B-D) [24]. These outcomes were consistent with pooled results from 4 anti-PD-1 monotherapy arms in trials of previously untreated late-stage NSCLC [19][20][21][22].…”
Section: Neoantigen Burden Correlates With Ici Responsesupporting
confidence: 84%
“…We simulated the growth of 100 NSCLC tumors and characterized their neoantigen clonal architectures using parameters derived from previous literature (Figure 1A, Table S1). To model the oligoclonality of anti-tumor adaptive immunity, the two most clonally expressed and immunogenic neoantigens at any given time were deemed TDAs, such that only cells harboring TDAs were at greater propensity to be eliminated[2, 22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct utilization of neoantigens as biomarkers would rely on the development of assays and algorithms that can precisely detect both the quantity and quality of neoantigens within a tumor. 411 …”
Section: Biomarkers For Immunotherapy—lessons From Icb and Car-t Cellsmentioning
confidence: 99%
“…Thus, neoantigens binding to multiple HLA may offer a therapeutic advantage. In addition, potent and dominant neoantigen-specific T cell response may favor the loss of neoantigen expression due to immune pressure [ 162 ]. Therefore, it remains to be shown that immunotherapy targeting neoantigens derived from more disruptive aberrations would generate long and lasting memory T cell responses.…”
Section: Discussionmentioning
confidence: 99%